Contemporary Challenges of Sustainable Transport in International Trade - Fajczak-Kowalska, Anita (Towards Sustainable Transport in Logistics and International Trade, 2025)
The aim of this chapter is to identify and classify the main barriers and challenges to sustainable transport in international trade, with a focus on Central and Eastern Europe. The authors apply the desk research method, analyzing current strategic documents and industry reports. The analysis identifies four key dimensions of the problem: environmental, social, technological, and economic-managerial. Despite the existence of coherent strategic frameworks at the international level, policy implementation faces multiple systemic obstacles, such as lack of interoperability, limited access to financing, infrastructure shortages, and transport exclusion. The main limitation of the study is the absence of primary data. Practical implications highlight the need for better sectoral integration, the implementation of digital standards, and stronger support for SMEs. From a social perspective, the chapter emphasizes the importance of mobility justice. The originality of the study lies in its systematic approach to the multidimensional challenges of transport in the Eurasian context and in identifying gaps between policy objectives and actual implementation.